2018
DOI: 10.1002/jca.21658
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the storm: A case of thyroid storm refractory to conventional treatment benefiting from therapeutic plasma exchange

Abstract: Thyroid storm is a severe manifestation of thyrotoxicosis characterized by systemic organ dysfunction secondary to a hypermetabolic state. Although antithyroid drugs, steroids, beta‐blockers, antipyretics, and cholestyramine are the standard of care, some patients inadequately respond to these conventional therapies. Therapeutic plasma exchange has been previously utilized as a treatment modality in patients with a poor response to routine therapies or with contraindications to them. Herein, we report our expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Five patients had an Impella device installed, and 9.3% had an intra-aortic balloon pump. Chaaya et al, Ahmad et al, and Korte et al reported the use of a left ventricular assist device [43,73,237]. In terms of other thyroid-related procedures, 18.6% of the patients underwent thyroidectomy, whereas 3.3% received RAI.…”
Section: Resultsmentioning
confidence: 99%
“…Five patients had an Impella device installed, and 9.3% had an intra-aortic balloon pump. Chaaya et al, Ahmad et al, and Korte et al reported the use of a left ventricular assist device [43,73,237]. In terms of other thyroid-related procedures, 18.6% of the patients underwent thyroidectomy, whereas 3.3% received RAI.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated the use of therapeutic plasma exchange to decrease the thyroid hormone levels in a patient with cardiogenic shock secondary to thyrotoxicosis [ 8 ]. It has been well documented that in patients with acute thyrotoxicosis, therapeutic plasma exchange can remove thyroid hormones as well as thyroid gland autoantibodies, catecholamines and cytokines [ 19 , 20 , 30 , 36 ]. In research by Subahi et al ., a four-step algorithm was created for the management of thyrotoxic crisis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%